Parish Priests and Marriage Cases - Kariyil, Antony (Journal of Dharma, 1980)
E. De Bekker W.F. and G Tayla W.F., Parish Priests and Marriage Cases, Bangalore: Theological Publications in India, 1978, pp. 239 +.